The vexed question of African languages in education. Still a solution may lay in front of us. Revisiting Orality for an authentic African future - (:unkn) unknown (My University, 2014)
Rather than attempting to translate the European curriculum into African languages, formal education in Africa should include authentic oral texts from each local tradition. This would contribute to language and cultural transmission. Giving precedence to orality would help solve the problem of dialectal choice and standard as local varieties could easily be used. In order to do that, school time could be divided between school proper and community sessions headed by selected adults, who would teach small groups of pupils. This would also alleviate the burden of teachers facing over crowded classrooms. The feasibility of this proposal is illustrated for South Africa.
Keywords: African Research